Comercio y contrabando en la frontera noreste, 1861-1865 - Fernández de Castro, Patricia (Frontera Norte, 2017)
En este artículo se examina la historia del comercio entre Texas y las poblaciones fronterizas de Tamaulipas, Nuevo León y Coahuila durante los años de la Guerra de Secesión norteamericana, desde la doble perspectiva del regionalismo y la articulación política y económica del centro del país y los estados del noreste. Este trabajo particulariza el caso de Matamoros, ya que ese puerto protagonizó este periodo de auge comercial, aunque los varios poblados de la frontera noreste participaron activamente en el intercambio fronterizo que floreció entre 1861 y 1865. ABSTRACT This article examines the history of trade between Texas and the border settlements of Tamaulipas, Nuevo León, and Coahuila during the Civil War. The analysis adopts a dual perspective: regionalism, on the one hand, and the political and economic ties between central Mexico and the states of the northeast, on the other. The work focuses on the case of Matamoros, since it played a central role in the trade boom of this period, although several towns along Mexico’s northeastern border with the United States also participated actively in the border trade that flourished between 1861 and 1865.